2018
DOI: 10.3389/fimmu.2018.02472
|View full text |Cite
|
Sign up to set email alerts
|

CD169+ Macrophages Capture and Dendritic Cells Instruct: The Interplay of the Gatekeeper and the General of the Immune System

Abstract: Since the seminal discovery of dendritic cells (DCs) by Steinman and Cohn in 1973, there has been an ongoing debate to what extent macrophages and DCs are related and perform different functions. The current view is that macrophages and DCs originate from different lineages and that only DCs have the capacity to initiate adaptive immunity. Nevertheless, as we will discuss in this review, lymphoid tissue resident CD169+ macrophages have been shown to act in concert with DCs to promote or suppress adaptive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 151 publications
(199 reference statements)
5
80
0
Order By: Relevance
“…26 In contrast, in non-intestinal lymphoid tissues, expression of CD169 by MPs can be driven by type-1 IFNs during viral infections but is constitutively expressed by marginal-zone and subcapsularsinus MPs that require B cell-produced LTα1β2, as well as RANK, LXR, and CSF-1 signaling. 39 Other specific signals that may be important for MP differentiation is implied by our analysis of regulons important for these divergent differentiation pathways, and upstream analysis of these pathways is complex, and currently being evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In contrast, in non-intestinal lymphoid tissues, expression of CD169 by MPs can be driven by type-1 IFNs during viral infections but is constitutively expressed by marginal-zone and subcapsularsinus MPs that require B cell-produced LTα1β2, as well as RANK, LXR, and CSF-1 signaling. 39 Other specific signals that may be important for MP differentiation is implied by our analysis of regulons important for these divergent differentiation pathways, and upstream analysis of these pathways is complex, and currently being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…We next determined the ability of these two colon MP subpopulations to capture systemic antigens, since prior studies had identified CD169 + MPs in the spleen and LNs as "gatekeepers" at the blood-LN interface. 38,39 F4/80 + cells closely associated with blood vessels avidly took up systemically administered 10kD dextran (Dex) ( Fig. 3c), which was further localized to the CD11c − CD169 + CD206 hi cell population ( Fig.…”
Section: Commensal Microbiota Globally Affects the Development And Gementioning
confidence: 99%
“…In coordination with DCs, CD169+ macrophages support CMI by providing antigen and producing type I IFN. However, CD169+ macrophages can suppress CMI to self‐antigens and phagosome‐restricted content including apoptotic cells and exosomes (Grabowska, Lopez‐Venegas, Affandi, & den Haan, ; McGaha, Chen, Ravishankar, van Rooijen, & Karlsson, ; Miyake et al, ; Saunderson, Dunn, Crocker, & McLellan, ). Indeed, several hours after infection, phagosome confined LLO‐minus bacteria are still localised to CD169+ macrophages, whereas bacteria growing in the host cytosol are transferred to CD8‐α + DCs that serve as a protective niche for bacterial survival (Edelson et al, ; Neuenhahn et al, ; Perez et al, ).…”
Section: What Makes L Monocytogenes Such a Potent Inducer Of Cd8+ T‐mentioning
confidence: 99%
“…In general, macrophages remain at the inflammatory sites to eliminate pathogens and apoptotic cells by phagocytosis and clearance and produce pro-inflammatory cytokines. In contrast, DCs can travel to the draining lymph nodes and stimulate T cells (28,29).…”
Section: The Effect Of Chondroitin Sulfate On Antigen-presenting Cellmentioning
confidence: 99%